1972
DOI: 10.1128/jvi.9.2.234-243.1972
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Virus Growth by Ouabain: Effect of Ouabain on the Growth of HVJ in Chick Embryo Cells

Abstract: The effect of ouabain (g-strophanthin), a cardiac glycoside, on the growth of several enveloped viruses was examined. It was found that the growth of HVJ (Sendai virus) in chick embryo cells was markedly inhibited by the drug at a concentration as low as 5 X 10-1 M. A virus-inhibitory concentration of ouabain did not cause morphological changes in uninfected cells, nor did it have the capacity to inactivate virus infectivity. Ouabain interfered with the intracellular synthesis of viral macromolecules. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…We also demonstrated that the Na + /K + /ATPase pump inhibitors, ouabain and lanatoside C, can inhibit the replication of influenza virus, NDV and VSV, representatives of three different RNA virus families. These data, combined with the results of previous studies that show inhibition of HSV-1, vaccinia virus, MuLV and Sendai virus (Deng et al, 2007;Dodson et al, 2007;Nagai et al, 1972;Tomita and Kuwata, 1978), indicate that these cardioactive glycosides have broad antiviral activity. Through the use of Vero cells, we determined that these compounds do not act by inducing interferon, as the same degree of virus inhibition was observed in these cells as seen in A549 cells.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We also demonstrated that the Na + /K + /ATPase pump inhibitors, ouabain and lanatoside C, can inhibit the replication of influenza virus, NDV and VSV, representatives of three different RNA virus families. These data, combined with the results of previous studies that show inhibition of HSV-1, vaccinia virus, MuLV and Sendai virus (Deng et al, 2007;Dodson et al, 2007;Nagai et al, 1972;Tomita and Kuwata, 1978), indicate that these cardioactive glycosides have broad antiviral activity. Through the use of Vero cells, we determined that these compounds do not act by inducing interferon, as the same degree of virus inhibition was observed in these cells as seen in A549 cells.…”
Section: Discussionsupporting
confidence: 66%
“…The Na + /K + /ATPase pump inhibitors, ouabain, lanatoside C, strophanthidin and digoxin were all identified as potential influenza virus inhibitors in the HTS. These cardioactive glycosides, which are used in the treatment of congestive heart failure and cardiac arrhythmia, have also been shown to inhibit the replication of herpes simplex virus (HSV) (Dodson et al, 2007), vaccinia virus (Deng et al, 2007), murine leukemia virus (MuLV) (Tomita and Kuwata, 1978) and Sendai virus (Nagai et al, 1972). To confirm our initial findings, we examined the ability of ouabain and lanatoside C to inhibit influenza virus replication.…”
Section: Inhibition Of Rna Viruses By Sodium Potassium Atpase Pump Inmentioning
confidence: 84%
“…Strophantine, cymarin, and digoxin are the most potent of the antipoxviral glycosides identified in the screen (IC 99 s of 70, 120, and 200 nM, respectively), whereas neriifolin is the least effective (IC 99 of 2 M). Strophantine has been reported to inhibit the growth of Sendai virus (36), and digoxin was recently found to inhibit replication of herpes simplex virus, varicella-zoster virus, cytomegalovirus, and adenovirus (21). Synthetic cardiac glycosides with antiherpes activity have also been reported previously (57,58).…”
Section: Resultsmentioning
confidence: 99%
“…The use of cardenolides to combat human cancers and reduce viral production has been previously explored (Diederich et al, 2017;Nagai et al, 1972;Platz et al, 2011;Su et al, 2008;Tomita and Kuwata, 1978). The binding of cardenolides to Na + /K + -ATPase not only inhibits the activity of the solute pump, but also results in the recruitment of Na + /K + -ATPase associated signalsomes in cancer cells, initiating the associated signaling pathways, and hence the anti-cardiovascular dysfunction and anti-cancer biological activities (Diederich et al, 2017;Newman et al, 2008;Prassas and Diamandis, 2008).…”
Section: Introductionmentioning
confidence: 99%